(untitled) (Palíndromo, 2025)
The text unfolds insights gathered from interviews with the pedagogical curator and mediators of the exhibition "Dos Brasis: Arte e Pensamento Negro," presented at Sesc Belenzinho between 2023 and 2024, in order to approach it from the perspective of its reception. A descriptive-analytical methodology is adopted to explore the possibility of cultural mediation addressing the racism expressed by sections of the audience in their responses to Afro-centric artistic works, with a view to treat it in more than one sense. To this end, an intersection with the psychoanalytic method is attempted, in which listening and dialogue allow, on the one hand, the repercussion of derogatory speeches and, on the other, their interrogation with the aim of exploring their origins. It is noted that the mediation developed within the exhibition, regarding racist manifestations, successfully practiced consistent forms of treatment through speech.